Assessing The Jurisdictional Legitimacy of International Criminal Court (ICC) in Arresting Head of State from Non-Party States to The Rome Statute (Case Study: The Problematics of Arresting Benjamin Netanyahu) - Dewic Sri Ratnaning Dhumillah; Jeremia Ricardo (Law Development Journal, 2026)
The issuance of an arrest warrant by the ICC for Israel Prime Minister Benjamin Netanyahu presents a fundamental juridical problem, given Israel's status as a non-State Party and Netanyahu's status as an active head of state. This research aims to (1) analyze the legal basis and legitimacy of the ICC's jurisdiction, and (2) analyze the resolution of the legal antinomy between the ICC's authority (Article 27) and the doctrine of head of state immunity (Customary International Law). This study employs a normative juridical methodology, utilizing statute, case, and conceptual approaches. The analysis reveals that the ICC's jurisdiction is legally valid, as it is not based on the perpetrator's nationality (ratione personae), but on the territorial delegation of jurisdiction (ratione loci) by Palestine as a State Party (Article 12(2)(a)), a basis confirmed by the 2021 Pre-Trial Chamber I decision. Furthermore, the study finds that the legal antinomy regarding immunity is resolved in favor of international criminal law. Head of state immunity (immunity ratione personae), rooted in the par in parem non habet imperium principle and the ICJ's 2002 Arrest Warrant case, is found to be inapplicable in the vertical relationship vis-à-vis an international court. This resolution is supported by Paragraph 61 of the Arrest Warrant decision itself and the ICC Appeals Chamber's 2019 judgment in the Al-Bashir (Jordan Referral) case. Thus, Article 27 (irrelevance of official capacity) prevails, and the ICC's legal basis for the arrest warrant is sound.